Staff development : a practical guide - Stewart, Andrea; Washington-Hoagland, Carlette; Zsulya, Carol T. (American Library Association, 2013)
Since its original publication more than two decades ago, this guide has remained a respected and practical handbook for supporting one of the most important assets libraries possess: their human resources. Staff development and training are not only important but essential to ensure that libraries meet new challenges and fulfill their missions, especially in a constantly changing world where technological innovations directly impact information access. This new edition offers unique, state-of-the-art perspectives on such important topics as: Building a staff development program, and strategies for developing staff; Tracking changes through training, including the importance of setting goals and needs assessments; Refining the customer service attitude; and Using instructional design for staff development.